Actions For Immediate Response To Antimicrobial Resistant Gonorrhoea: A Case Analysis Exemplar Using The Modified Depestel Framework - Tabuena, Almighty C. (Medical Science Journal for Advance Research, 2021)
Antimicrobial resistance (AMR) is a growing global issue that causes significant morbidity. AMR causes more serious infections and consequences, increasing hospital stays and death. AMR threatens to undermine our capacity to cure common infectious infections. In this case, a clinician at a local sexual health clinic has recently alerted a 35-year-old male who has been seen in the clinic with probable AMR gonorrhoea. Consider the case's immediate consequences and select three measures to be addressed within the first several weeks. This article used the DEPESTEL (demographic structures, epidemiological patterns, political factors, economic influences, sociological trends, technological innovations, educational factors, and legislative requirements) framework to construct the response. In conclusion, AMR gonorrhoea infections stay in the body, increasing infection risk. Rapid gonorrhoea patient diagnosis is crucial for public health and clinical care of infected patients and sexual partners. Patients must be treated to cease transmission. AMR surveillance must include seasonal and epidemiological data. Keep track of treatment failures, warn partners, and prioritize clinical care. To appropriately analyze and handle treatment failure scenarios, cross-border collaboration is essential. Traveling overseas increases AMR gonorrhoea risk. Fear of AMR in the population may cause over-reaction to STIs. The media might assist in disseminating this vital health prevention, management, and security messages. People at risk need to be informed about the possibility of resistant gonorrhoea. Age, sex, sexual orientation, specimen location, prior infections, and concurrent STIs are also needed to be better reported.